Relationship between moral sensitivity and the quality of nursing care for the elderly with Covid-19 in Iranian hospitals - Shima Nazari; Sarieh Poortaghi; Farshad Sharifi; Shaghayegh Gorzin; Pouya Farokhnezhad Afshar (BMC, 2022)
Abstract Background The quality of care has a significant impact on the condition of elderly patients. Many factors affect the quality of care, including ethical considerations. Ethical considerations, such as moral sensitivity, change in times of crisis. The present study was conducted to assess the relationship between moral sensitivity and the quality of nursing care for the elderly with Covid-19 in Iranian hospitals. Methods This was a cross-sectional descriptive correlational study. The participants included 445 nurses that were selected by quota sampling method from hospitals admitting COVID-19 patients. The data were collected using the Moral Sensitivity Questionnaire (MSQ) and Quality Patient Care Scale (QUALPAC) as self-reports. We used the SPSS software v.16 for statistical analysis. Results The total score of moral sensitivity and quality of care was 52.29 ± 16.44 and 2.83 ± 0.23, respectively. Moral sensitivity negatively correlates with psychological, social, and physical aspects (P < 0.05). Modifying autonomy, interpersonal orientation, and experiencing moral conflict predicted β = 0.10 of the psychosocial aspect of quality of care. Structural moral meaning and expressing benevolence predicted the changes in the physical dimension of quality of care (β = 0.02). Conclusion The quality of care had a significant inverse correlation with moral sensitivity. Multiple regression analysis showed that modifying autonomy, interpersonal orientation, and experiencing moral conflict could predict the psychosocial dimensions. Structuring moral meaning could predict the physical dimension. The communication aspects were not related to any of the dimensions of moral sensitivity.